LEARNING A FOREIGN LANGUAGE AND THE LANGUAGE TOURISM EXPERIENCE - Makhmudov, Kudratbek (Журнал иностранных языков и лингвистики, 2021)
The article discusses second language learning and its advantages as well as general aspects that need to be addressed in language tourism